"International Migration" between empire and nation. The statistical construction of an ambiguous global category in the International Labour Office in the 1920s. (June 2019) - Stricker, Yann
This article inquires into the historical conditions of the global category of "international migration" by analysing quantification processes in the International Labour Organization in the 1920s. Based on a history of knowledge perspective, it analyses how and why the categories of immigration and emigration were reduced to the single category of "international migration". The paper interprets this epistemological change with a shift from an imperial to an international point of view that occurred in the 1920s. This argument is based on an analysis of negotiations between international administrators and functionaries of the British Empire that arose, when international categorisation and quantification of people on the move began. Drawing on sources from the British National Archives and the International Labour Organization, this article highlights the historical importance of debates about the categories of "nation" and "race", in the making of what was stabilized only later in the 20th century as the category of "international migration".